Compensating employees who suffer work-related psychiatric harm in the course and scope of their employment - Du Plessis, Meryl Candice (Rhodes University, Faculty of Law, Law, 2008)
This study aims to ascertain the legal redress available to employees who suffer psychological harm as a result of workplace stress. On a general level, it identifies and assesses some of the available policy options, particularly as they relate to the interaction of statutory workers' compensation schemes and the common law. On a more specific level, it examines and analyses various issues: the nature and extent of compensable psychiatric harm; the legal duty on employers to protect employees' health and well being; the role of negligence; requirements specific to the Compensation for Occupational Injuries and Diseases Act 130 of 1993 (COIDA); and the causal nexus necessary to sustain a claim. The conclusion is reached that employees should utilise the workers' compensation system as the primary vehicle to obtain redress if they suffer from occupational psychiatric harm. However, due to the law's generally conservative approach to psychiatric harm and intimations that the Department of Labour intends setting strict requirements for claims for psychiatric harm in terms of COIDA, the common law of delict might continue to play an important role in claims for occupational psychiatric harm. The writer recommends that a hybrid system for compensation for stress-related psychiatric harm suffered in the course and scope of employment be adopted, with the statutory compensation scheme providing relatively limited benefits and the common law providing general damages if the claimant can prove negligence on the part of the employer; that the requirement of a recognised psychiatric illness be maintained for both statutory compensation and compensation in terms of the common law; that all parties' interests are carefully balanced in delineating the employer's legal duty to employers and that undue weight not be accorded to the terms of the contract of employment; that more attention be paid to factual causation and the development of lternatives/complements to the traditional conditio sine qua non test; that the validity of the circular instruction on post-traumatic stress disorder (PTSD) be tested on administrative-law grounds; and that the stringent prescription requirements set by the circular instruction on PTSD be reviewed.
Keywords: Workers' compensation -- Law and legislation; Liability for emotional distress; Post-traumatic stress disorder; Occupational diseases